PERMASALAHAN DALAM PEMBELAJARAN BAHASA ARAB PADA KELAS VIII MTS ALHASYIMIYAH GERUNG LOMBOK BARAT - Shaddiq, Mohamad Shabirin (Indonesian Society and Religion Research, 2025)
The objective of this study is to identify the problems in Arabic language learning at Madrasah Tsanawiyah (Islamic junior high schools) for grade VIII. One example is Madrasah Tsanawiyah (MTs) Alhasyimiyah, which faces challenges in teaching Arabic to grade VIII students. These challenges include a lack of student motivation and interest in Arabic, limited resources and facilities, insufficient use of technology in learning, restricted learning time, teachers' lack of skills in teaching Arabic, and insufficient parental support and involvement. This research is based on observations and direct interviews with several informants and employs a qualitative research method, which is naturalistic and reveals the problems as they are without manipulation.